Global Research Alliance N2O chamber methodology guidelines: Considerations for automated flux measurement. Issue 5 (8th September 2020) - Grace, Peter R.; van der Weerden, Tony J.; Rowlings, David W.; Scheer, Clemens; Brunk, Christian; Kiese, Ralf; Butterbach‐Bahl, Klaus; Rees, Robert M.; Robertson, G. Philip; Skiba, Ute M.
Abstract: Nitrous oxide (N2 O) emissions are highly episodic in response to nitrogen additions and changes in soil moisture. Automated gas sampling provides the necessary high temporal frequency to capture these emission events in real time, ensuring the development of accurate N2 O inventories and effective mitigation strategies to reduce global warming. This paper outlines the design and operational considerations of automated chamber systems including chamber design and deployment, frequency of gas sampling, and options in terms of the analysis of gas samples. The basic hardware and software requirements for automated chambers are described, including the major challenges and obstacles in their implementation and operation in a wide range of environments. Detailed descriptions are provided of automated systems that have been deployed to assess the impacts of agronomy on the emissions of N2 O and other significant greenhouse gases. This information will assist researchers across the world in the successful deployment and operation of automated N2 O chamber systems.